Hair thread tourniquet syndrome. Three cases in ten years. - Cutrone, M.; Magagnato, L. (European Journal of Pediatric Dermatology, 2009)
Three cases of hair thread tourniquet syndrome are here reported. The syndrome is clinically characterized by a suddenly arising constriction of a finger or toe or genitalia, which is secondary to twisting of a hair or textile fibers around the involved segment. The Authors underline the need for an early diagnosis and treatment of this syndrome, which can lead to mutilation of the involved segment.